pengaruh pemangkasan dan pemupukan NPK terhadap tanaman pare (Momordica charantia L.) - Alifatul Laela Mauliddiana; Usmadi Usmadi (Berkala Ilmiah Pertanian, 2022)
Pare Plant is a type of horticultural plant originating from the cucurbitaceae family. Bitter gourd contains antioxidants that help suppress the inflammatory response and lower glucose levels in diabetes. Cultivation of bitter melon by using pruning and the use of NPK fertilizer can increase production yields. Pruning on plants needs to be done in order to increase the number of flowers produced by plants. NPK fertilizer is a macro nutrient needed by plants to be able to grow and metabolic processes in plants can run well. This research was conducted in the Patrang sub-district, Patrang sub-district, Jember district which was carried out from March to June 2021. This research method used a completely randomized design (RAL) with a 4x3 factorial design which was repeated 3 times. The first factor is pruning which consists of 3 levels of treatment P1 (without pruning), P2 (3 branches pruning on segments 1-3 and P3 (6 pruning branches on sections 1-6), and the second factor is the dose of NPK fertilizer which consists of 4 The treatment levels were N1 (0 g/plant), N2 (10g/plant), N3 (20 g/plant) and N4 (30 g/plant). The experimental results showed that there was an interaction effect on NPK fertilization with pruning which gave very significant different results to fruit diameter. The effect of NPK fertilizer application was significantly different on fruit length and fruit volume. In the treatment, the effect of giving NPK fertilizer was not significantly different on the initial appearance of flowers, the number of fruits and significantly different on the number of fruits.